EFFECT OF COLLABORATIVE INQUIRY LEARNING MODEL TO 4C STUDENT SKILLS IN HIGH SCHOOL - Hani Diana Sipayung; Rahmatsyah .; Ridwan Abdullah Sani; Wawan Bunawan; Rajo Hasim Lubis (Universitas Negeri Medan, 2019)
This study aims to analyze the effect of collaborative inquiry learning models in improving students' 4C (Collaboration, Communication, Critical Thinking and Creativity) skills for learning physics on impulses, momentum and collisions. The population of this study were all students of class X of SMA Negeri 7 Medan in the second semester of the 2017/2018 academic year. The sampling technique in this research used cluster random class, the experimental class used collaborative inquiry learning model and control class using conventional learning. The variables in the study consisted of 4C skills as dependent variables and collaborative inquiry models as independent variables. The data in this study were analyzed using one-party t-test. The results showed that students '4C skills with collaborative inquiry learning models were better than students' 4C skills with conventional learning